2006
DOI: 10.1038/sj.mp.4001824
|View full text |Cite
|
Sign up to set email alerts
|

Mice with neuron-specific accumulation of mitochondrial DNA mutations show mood disorder-like phenotypes

Abstract: There is no established genetic model of bipolar disorder or major depression, which hampers research of these mood disorders. Although mood disorders are multifactorial diseases, they are sometimes manifested by one of pleiotropic effects of a single major gene defect. We focused on chronic progressive external ophthalmoplegia (CPEO), patients with which sometimes have comorbid mood disorders. Chronic progressive external ophthalmoplegia is a mitochondrial disease, which is accompanied by accumulation of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 57 publications
6
136
0
1
Order By: Relevance
“…We showed that transgenic mice with neuron-specific expression of mutant Polg1 displayed BD-like phenotypes. 23 The present finding suggests that reduced expression of POLG1, in addition to mutations of POLG1, is relevant to BD.…”
Section: Biomarkers Of Bipolar Disorder T Kato Et Alsupporting
confidence: 54%
See 2 more Smart Citations
“…We showed that transgenic mice with neuron-specific expression of mutant Polg1 displayed BD-like phenotypes. 23 The present finding suggests that reduced expression of POLG1, in addition to mutations of POLG1, is relevant to BD.…”
Section: Biomarkers Of Bipolar Disorder T Kato Et Alsupporting
confidence: 54%
“…Mitochondrial DNA deletion syndrome can accompany BD and depression, 22 and an animal model carrying a mutation in one of these genes (Polg1) showed BD-like behavioral phenotypes. 23 POLG1 (polymerase-g catalytic subunit), WFS1 (Wolfram syndrome 1), POLG2 (polymerase-g accessory subunit), SLC25A4 (ANT1, adenine nucleotide translocator 1) and Twinkle (C10orf2; mitochondrial DNA helicase).…”
Section: Candidate Biomarker Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, mitochondrial dysfunction is increasingly being noted in schizophrenia, bipolar disorder and other mood disorders, based on the expression pattern of mitochondria related genes, as well as on morphological and biochemical analysis of mitochondrial function in patients [41][42][43] and animal models. 44 …”
Section: Discussionmentioning
confidence: 99%
“…That work was subsequently extended to look at the gene expression changes in blood from the animals on the different treatments, as a way of identifying brain-blood biomarkers [Le-Niculescu et al, 2009b]. Niculescu et al, 2008Niculescu et al, , 2011b Nile grass rat [Ashkenazy-Frolinger et al, 2010] Methamphetamine [Niculescu et al, 2000;Macedo et al, 2013] Learned helplessness [Mingmalairak et al, 2010] CLOCK [Roybal et al, 2007;Mukherjee et al, 2010;Arey et al, 2013] Flinders Sensitive Line (FSL) rats [Malkesman and Weller, 2009] Methamphetamine/valproate [Ogden et al, 2004] Isolation housing [Le-Niculescu et al, 2008;Niwa et al, 2013] CTNNB1 [Gould et al, 2008] Wistar Kyoto (WKY) rats [Will et al, 2003;Malkesman and Weller, 2009] Amphetamine-chlordiazepoxide [Kelly et al, 2009] Forced swim test [Le-Niculescu et al, 2008] POLG [Kasahara et al, 2006;Kubota et al, 2010] Madison (MSN) [Saul et al, 2012] Lithium [Gould et al, 2007;Johnson et al, 2009;Kovacsics and Gould, 2010] Tail suspension test [Le-Niculescu et al, 2008] HINT1 [Barbier and Wang, 2009] Other mood stabilizers: Lamotrigene [Li et al, 2010], Topiramate [Bourin et al, 2009] Restraint stress [Johnson et al, 2009;Koo et al, 2010] GRIN2A [Taniguchi et al, 2009] Ouabain [Herman et al, 2007] Shock-induced aggression …”
Section: Animal Modelsmentioning
confidence: 99%